Pendampingan Perencanaan Fasilitas Wisata Pantai Pasir Putih di Kolaka Utara - Hidayat, Arman; Puspaningtyas, Retno; Masgode, Muhammad Buttomi; Rustan, Fathur Rahman; Ola, Mursalim Ninoy La (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
Pasir Putih Beach in Kolaka Utara possesses considerable potential as a leading tourist destination. Nonetheless, insufficient infrastructure continues to pose a significant obstacle to attracting additional visitors. This community service initiative seeks to develop tourism infrastructure that meets the need of local populations and adheres to sustainable principles. The Participatory Action Research methodology was utilized to guarantee active community engagement in identifying demands, doing analysis, and planning facilities. The phases of the activity encompassed field observation, focus group discussions, planning, and community validation. The result of this action is a planning document that includes facility designs, cost estimates, implementation timelines, and management strategies. The proposed amenities comprise public restrooms, parking zones, seating arrangements, informational displays, and divided garbage receptacles. The transfer of the planning document to local authorities constitutes the preliminary phase of participatory implementation. This strategy not only produces facilities that address community requirements but also enhances awareness and cultivates a sense of ownership among residents concerning the stewardship of Pasir Putih Beach. This effort aims to foster sustainable tourism development, enhance tourist visitation, and yield economic advantages for the local community